2015
DOI: 10.1055/s-0035-1551672
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Prenatal, Onward, and Postdischarge Experiences in Case of Extreme Prematurity: When to Set the Course for a Trusting Relationship between Parents and Medical Staff

Abstract: This study stresses the impact of prenatal counseling and shows that, regardless of outcome, the course of a trusting relationship between parents and health care team is already set before birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Rothe et al 51 recommend initial prenatal contact between the caregiver and the parents and a prenatal consultation to help parents feel secure and reduce their concerns. Bornhorst et al 52 showed that involving parents in prenatal decision-making increased their feeling of involvement in the postnatal treatment of their child, and concluded that the course of a trusting relationship between parents and HCP is set before birth. 52 Studies on transitional care found that an intensive relationship between the APN and those in care can improve patient outcomes, significantly increase the chances patients will survive, and reduce rehospitalizations.…”
Section: Parental Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Rothe et al 51 recommend initial prenatal contact between the caregiver and the parents and a prenatal consultation to help parents feel secure and reduce their concerns. Bornhorst et al 52 showed that involving parents in prenatal decision-making increased their feeling of involvement in the postnatal treatment of their child, and concluded that the course of a trusting relationship between parents and HCP is set before birth. 52 Studies on transitional care found that an intensive relationship between the APN and those in care can improve patient outcomes, significantly increase the chances patients will survive, and reduce rehospitalizations.…”
Section: Parental Supportmentioning
confidence: 99%
“…Bornhorst et al 52 showed that involving parents in prenatal decision-making increased their feeling of involvement in the postnatal treatment of their child, and concluded that the course of a trusting relationship between parents and HCP is set before birth. 52 Studies on transitional care found that an intensive relationship between the APN and those in care can improve patient outcomes, significantly increase the chances patients will survive, and reduce rehospitalizations. 17 In the TtH-model, APN support includes intensive, long-term parental support.…”
Section: Parental Supportmentioning
confidence: 99%